2019
DOI: 10.2166/nh.2019.170
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the impact of agricultural crops on the spatial and seasonal variability of water balance components in the Lake Tana basin, Ethiopia

Abstract: The Lake Tana basin hosts more than three million people and it is well known for its water resource potential by the Ethiopian government. The major economic activity in the region is agriculture, but the effect of agricultural crops on water resources is poorly understood. Understanding the crop water interaction is important to design proper water management plans. Therefore, the primary objective of this research is to investigate the effect of different agricultural crops on the spatial and seasonal varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Note that "r_" represents adding 1 from the fitted value and multiply the result with the parameters initial value; "v_" indicates changing the initial value with the fitted value; "a_" indicates adding the fitted value to the initial model value ARRC Cultivated land, FRST Forest, RNGE Grassland, RNGB Shrubland daily and monthly time steps in the three watersheds of the Lake Tana Sub Basin (i.e., Gilegel Abay, Gumara and Rib watersheds), Tigabu et al (2019) reported that the model is generally better in the monthly time step simulations.…”
Section: Sensitivity Analyses and Model Calibration And Validationmentioning
confidence: 99%
“…Note that "r_" represents adding 1 from the fitted value and multiply the result with the parameters initial value; "v_" indicates changing the initial value with the fitted value; "a_" indicates adding the fitted value to the initial model value ARRC Cultivated land, FRST Forest, RNGE Grassland, RNGB Shrubland daily and monthly time steps in the three watersheds of the Lake Tana Sub Basin (i.e., Gilegel Abay, Gumara and Rib watersheds), Tigabu et al (2019) reported that the model is generally better in the monthly time step simulations.…”
Section: Sensitivity Analyses and Model Calibration And Validationmentioning
confidence: 99%
“…Estimates have been published for several of the East African lakes. Most estimates are for Lake Victoria (Swenson and Wahr 2009;Vanderkelen et al 2018;Kizza et al 2012;Tate et al 2004;Yin and Nicholson 1998) and Lake Tana (Tigabu et al 2019;Rientjes et al 2011;Wale et al2009;Chebud and Melesse 2009;Kebede et al 2006). Estimates have also been made for Lake Tanganyika (Bergonzini et al 2002), Lake Turkana (Velpuri et al 2012), Lake Malawi (Lyons et al 2011), Lake Kivu (Bergonzini 1998;Muvundja et al 2014), Lake Rukwa (Bergonzini 1998), and Lake Edward (Lehman 2002).…”
Section: Introduction To the Problemmentioning
confidence: 99%
“…1 ), with an elevation of 2744 m. The area has an estimated mean annual rainfall of 1280 mm and an annual average air temperature of 20 °C. The topography of the surrounding landscape varies significantly from lowland flood plains in the southwest to rugged mountains in the northeast, with a highly heterogeneous soil type dominated by agricultural lands ( Tigabu et al, 2019 ).
Figure 1 Map of Tis-Abay Waterfall.
…”
Section: Methodsmentioning
confidence: 99%